ChemInform Abstract: Copper(I)‐Catalyzed Alkylation of Aryl‐ and Alkenylsilanes Activated by Intramolecular Coordination of an Alkoxide. Issue 17 (28th April 2014) - Tsubouchi, Akira; Muramatsu, Daisuke; Takeda, Takeshi
Abstract The copper(I)‐catalyzed cross‐coupling of alkenyl‐ and arylsilanes with primary alkyl iodides as well as allylic and benzylic halides as electrophilic coupling partners is realized by intramolecular activation through alkoxide coordination.